Large-scale identification of novel transcriptional regulators of the aliphatic glucosinolate pathway in Arabidopsis - Chen, Lin (Journal of experimental botany, 2024)
© The Author(s) 2023. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.